Simultaneous Knockdown of Sprouty2 and PTEN Promotes Axon Elongation of Adult Sensory Neurons - Jamsuwan, Sataporn; Klimaschewski, Lars; Hausott, Barbara (Frontiers in Cellular Neuroscience, 2020)
Sprouty2 (Spry2) and phosphatase and tensin homolog deleted on chromosome 10 (PTEN) are both well-established regulators of receptor tyrosine kinase (RTK) signaling, and knockdown of Spry2 or PTEN enhances axon regeneration of dorsal root ganglia (DRG) neurons. The major role of Spry2 is the inhibition of the rat sarcoma RAS/extracellular signal-regulated kinase (ERK) pathway, whereas PTEN acts mainly as an inhibitor of the phosphoinositide 3-kinase (PI3K)/Akt pathway. In non-neuronal cells, Spry2 increases the expression and activity of PTEN, and PTEN enhances the amount of Spry2 by the inhibition of the microRNA-21 (miR-21) that downregulates Spry2. Applying dissociated DRG neuron cultures from wild-type or Spry2 deficient mice, we demonstrate that PTEN protein was reduced after 72 hours during rapid axonal outgrowth on the laminin substrate. Furthermore, PTEN protein was decreased in DRG cultures obtained from homozygous Spry2-/- knockout mice. Vice versa, Spry2 protein was reduced by PTEN siRNA in wild-type and heterozygous Spry2+/- neurons. Knockdown of PTEN in DRG cultures obtained from homozygous Spry2-/- knockout mice promoted axon elongation without increasing axonal branching. Activation of Akt, but not ERK, was stronger in response to PTEN knockdown in homozygous Spry2-/- DRG neurons than in wild-type neurons. Together, our study confirms the important role of the signaling modulators Spry2 and PTEN in axon growth of adult DRG neurons. Both function as endogenous inhibitors of neuronal growth factor signaling, and their simultaneous knockdown promotes axon elongation more efficiently than the single knockdown of each inhibitor. Furthermore, Spry2 and PTEN are reciprocally downregulated in adult DRG neuron cultures. Axon growth is influenced by multiple factors and our results demonstrate that the endogenous inhibitors of axon growth, Spry2 and PTEN, are co-regulated in adult DRG neuron cultures. Together, our data demonstrate that combined approaches may be more useful to improve nerve regeneration than targeting one single inhibitor of axon growth.